2014
DOI: 10.1039/c4cp02334j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic interactions leading to a complex interplay between bioelectrocatalytic properties and multilayer meso-organization in layer-by-layer assemblies

Abstract: The present study explores the development of mesostructured bioelectrochemical interfaces with accurate compositional and topological control of the supramolecular architecture through the layer-by-layer assembly of ternary systems based on poly(allylamine) containing an osmium polypyridyl complex (OsPA), an anionic surfactant, sodium dodecyl sulfate (SDS) or sodium octodecyl sulfate (ODS), and glucose oxidase (GOx). We show that the introduction of the anionic surfactant allows a sensitive increase of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…For example, osmium polypyridyl complex, sodium dodecyl sulfate (SDS), and glucose oxidase were used to form a multicomposite multilayer assembly that was driven by hydrophobic as well as electrostatic interactions. 26 Cyclic voltammetry showed a linear increase of the redox signals up to 4 ‘dipping cycles’, while a 3-fold increase in glucose oxidase coverage was seen with SDS that led to a 9-fold increase in sensitivity for the detection of glucose at a sensitivity of 18.4 μA cm –2 per layer. 26 …”
Section: Multilayer Protein Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, osmium polypyridyl complex, sodium dodecyl sulfate (SDS), and glucose oxidase were used to form a multicomposite multilayer assembly that was driven by hydrophobic as well as electrostatic interactions. 26 Cyclic voltammetry showed a linear increase of the redox signals up to 4 ‘dipping cycles’, while a 3-fold increase in glucose oxidase coverage was seen with SDS that led to a 9-fold increase in sensitivity for the detection of glucose at a sensitivity of 18.4 μA cm –2 per layer. 26 …”
Section: Multilayer Protein Assembliesmentioning
confidence: 99%
“…26 Cyclic voltammetry showed a linear increase of the redox signals up to 4 ‘dipping cycles’, while a 3-fold increase in glucose oxidase coverage was seen with SDS that led to a 9-fold increase in sensitivity for the detection of glucose at a sensitivity of 18.4 μA cm –2 per layer. 26 …”
Section: Multilayer Protein Assembliesmentioning
confidence: 99%
“…In recent years, the modification of solid‐state nanopores via polyelectrolyte assembly/adsorption has gained increasing interest . The LbL assembly of polyelectrolytes represents a very simple and versatile chemical method to create functional thin films with nanoscale precision . This functionalization method is based on the alternate deposition of polyanions and polycations on solid surfaces leading to the formation of polyelectrolyte multilayers .…”
Section: Functionalization Of Solid‐state Nanoporesmentioning
confidence: 99%
“…31 For instance, it has been shown that the presence of surfactants in LbL assemblies has a strong impact on structure−property relationship composite. 30,32,33 On the other hand, the surfactant character may disperse building blocks and enhance the interchain interactions between conducting polymer. 34 In this sense, the integration of CTAB into the LbL structure may promote structural changes with implications on the electronic conductivity of the films compared with the long chain polyelectrolyte PDADMAC.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Both cationic blocks are electrochemically inactive and have positive charge consisting of quaternary amines but with different mesogenic and surfactant characters, which may lead to different structure. , On the one side, the mesogenic character is the property of some compounds to promote molecular order or spatial orientation of the structures generated in combination with other reagents such as polymers . For instance, it has been shown that the presence of surfactants in LbL assemblies has a strong impact on structure–property relationship composite. ,, On the other hand, the surfactant character may disperse building blocks and enhance the interchain interactions between conducting polymer . In this sense, the integration of CTAB into the LbL structure may promote structural changes with implications on the electronic conductivity of the films compared with the long chain polyelectrolyte PDADMAC.…”
Section: Introductionmentioning
confidence: 99%